2004
DOI: 10.1016/j.humimm.2003.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of HLA-DRB1 alleles on lymphoproliferative responses to a naturally processed and presented measles virus phosphoprotein in measles immunized individuals

Abstract: Identification of stimulatory T-cell epitopes recognized by CD4+ T lymphocytes is important for vaccine development. Our previous studies using mass spectrometry identified a naturally processed HLA class II restricted DRB1*0301 T cell epitope in the measles virus phosphoprotein, MV-P1 (residues 179-197). Here we provide lymphocyte proliferation data from peripheral blood mononuclear cells (PBMC) obtained from 131 HLA-DRB1*0301-positive and HLA-DRB1*0301-negative (HLA discordant) individuals previously immuniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Our statistical approach and the description of the statistical analyses and methods are nearly identical to what we have previously published (16,(18)(19)(20)(21)(22). Data were descriptively summarized using frequencies and percentages for all categorical variables and medians and interquartile ranges (IQR) for all continuous variables.…”
Section: Methodsmentioning
confidence: 99%
“…Our statistical approach and the description of the statistical analyses and methods are nearly identical to what we have previously published (16,(18)(19)(20)(21)(22). Data were descriptively summarized using frequencies and percentages for all categorical variables and medians and interquartile ranges (IQR) for all continuous variables.…”
Section: Methodsmentioning
confidence: 99%
“…Fresh PBMCs from donors were used to optimize many variables including incubation times, antigen concentrations, and technique according to relevant findings in the literature [1,8,4]. Briefly, peripheral blood mononuclear cells (PBMC) were isolated from healthy donors within one hour of collection using standard Ficoll-Paque ™ procedures.…”
Section: Methodsmentioning
confidence: 99%
“…This is in concordance with other studies showing that certain HLA class I and II type alleles were associated with antibody [54] or CMI responses [55] following MCV. More research focusing on components of the measles virus that generate CMI responses in individuals with a specific HLA type have been undertaken [56]. In contrast, a Brazilian study showed a high rate of secondary vaccine failures that may be due to the use of different vaccines or oversensitivity of the test used to detect the nature of vaccine failure [57].…”
Section: Vaccine Failuresmentioning
confidence: 99%